Fruit size, mineral composition and quality of trickle-irrigated tomatoes as affected by potassium rates - Fontes, Paulo Cezar Rezende; Sampaio, Regynaldo Arruda; Finger, Fernando Luiz (Pesquisa Agropecuaria Brasileira, 2000)
An experiment was conducted to determine the fruit size, mineral composition and quality of trickle-irrigated tomatoes as affected by potassium fertilizer rates. Six potassium (K) rates were applied as KCl, corresponding to 0, 48.4, 118.6, 188.8, 259.0 and 399.4 kg ha-1, with four replicates, following a randomized block design. Quadratic responses to K rates were observed for double extra large (diameter > 60 mm), extra large (56 to 60 mm) and large (52 to 56 mm) fruit yields. Maximum yields of these classes were achieved with K rates of 116, 190 and 233 kg ha-1, respectively. Fruit dry matter, phosphorus, sulfur and magnesium contents were not affected by K rates, but nitrate and K contents showed significant increments as K rates were increased. Vitamin C, total soluble solids, lycopene and b-carotene contents in the fruits were not affected by K rates. Increments in the K rate lowered the fruit pH and increased total acids content.